2001
DOI: 10.1159/000048038
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-2-Macroglobulin Inhibits the Anticoagulant Action of Activated Protein C in Cord and Adult Plasma

Abstract: Healthy newborns have a very low risk of thrombosis. It has been suggested that this is partly due to the anticoagulant effect of alpha-2-macroglobulin (a2-M). This broad-spectrum protease binding glycoprotein is physiologically elevated in newborns over adult values and has been shown to complex generated alpha-thrombin. In our present study, we point out that a2-M also acts as a procoagulant by inhibiting activated protein C (APC). In all experiments performed in cord and adult plasma the anticoagulant actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Another explanation for the diminished capability of the postexercise PPP samples to generate thrombin might be exercise-induced elevated levels of antithrombin (AT) or alpha 2-macroglobulin (a2-M), the two most efficient inhibitors of thrombin (4). A dose-dependent decrease of ETP in the presence of increasing amounts of AT and a2-M has been shown previously (13). In the present study AT and a2-M plasma levels were not determined.…”
Section: Discussionsupporting
confidence: 52%
“…Another explanation for the diminished capability of the postexercise PPP samples to generate thrombin might be exercise-induced elevated levels of antithrombin (AT) or alpha 2-macroglobulin (a2-M), the two most efficient inhibitors of thrombin (4). A dose-dependent decrease of ETP in the presence of increasing amounts of AT and a2-M has been shown previously (13). In the present study AT and a2-M plasma levels were not determined.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, Cvirn et al. [13–15] have shown that high concentrations of α2MG in the presence of physiologic amounts of antithrombin suppress the anticoagulant action of APC, thereby enhancing the prothrombin activation and thrombin potential in cord and adult plasma. In the present study, prothrombin fragment f1.2 as a marker of thrombin generation was routinely investigated in patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…By inhibiting the formation of thrombin, APC also acts as an indirect anti-inflammatory agent [9]. Several components of the haemostatic system have been shown to modulate the anticoagulant action of APC [10][11][12]. In this study we focus on the possible synergistic anticoagulant effects of rhAPC and unfractionated heparin (UH) or rhAPC and melagatran.…”
Section: Introductionmentioning
confidence: 99%